2016
DOI: 10.4172/1948-5956.1000421
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide: Friend or Foe in Cancer Chemotherapy and Drug Resistance: A Perspective

Abstract: A successful treatment of cancers in the clinic has been difficult to achieve because of the emergence of drug resistant tumor cells. While various approaches have been tried to overcome multi-drug resistance, it has remained a major road block in achieving complete success in the clinic. Extensive research has identified various mechanisms, including overexpression of P-glycoprotein 170, modifications in activating or detoxification enzymes (phase I and II enzymes), and mutation and/or decreases in target enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…There are numerous mechanisms of NO stimulating cell proliferation, including increased mitogen-activated protein kinase pathway. A multitude of studies emphasizes that NO alone can induce cell death, and can be combined with several clinical anticancer drugs to enhance/sensitize their activity against a variety of human malignancies (30). A significant dissimilarity is demonstrated in plasma NO concentration between the CRC cases BT and those AT, for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous mechanisms of NO stimulating cell proliferation, including increased mitogen-activated protein kinase pathway. A multitude of studies emphasizes that NO alone can induce cell death, and can be combined with several clinical anticancer drugs to enhance/sensitize their activity against a variety of human malignancies (30). A significant dissimilarity is demonstrated in plasma NO concentration between the CRC cases BT and those AT, for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide ( ● NO), produced intracellularly via NOS catalysis, has been shown to kill tumor cells both in vitro and in vivo [46]. We have shown that ● NO/ ● NO-related species ● NO/ ● NO-related species nitrosylates both topo I and II while inhibiting the functions of only topo II [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Lowering ovarian cancer chemoresistance by NO/RNS involves, among others competition with cisplatin for the glutathione [71], decreasing activity of STAT3 and AKT signaling proteins [48,72], induction of DNA damage [50,51,52], inhibition of DNA repair protein activity [24,52,53], induction of apoptosis through, e.g., activation of p53 pathway, down-regulation of anti-apoptotic proteins or activation of Fas receptor [25,73]. On the other hand, NO/RNS can enhance drug resistance of cancer cells by various mechanisms, such as inhibition of apoptosis through, e.g., inhibition of caspase activity or increase in Bcl-2 expression [22], up-regulation of activity of proteins repairing DNA strand breaks [74] or lowering death receptors (CD95) exposure on cell surface by cGMP-dependent phosphorylation of syntaxin 4 [75] [Figure 4].…”
Section: Inos Expression Versus Chemoresistance In Ovarian Cancer mentioning
confidence: 99%